Evaluation of School of health students' ethics position in Turkey - Şen, Emine (Nursing ethics, 2017)
Background:The advances in science and technology increasingly lead to the appearance of ethical issues and to the complexity of care. Therefore, it is important to define the ethics position of students studying in health departments so that high quality patient care can be achieved.Objectives:The aim of this study was to examine the ethics position of the students at Shool of Health of an University in western Turkey.Methods:The study design was descriptive and cross-sectional. The study population included 540 first, second, third, and fourth year students from the Departments of Nursing, Midwifery, and Rescue and Disaster Management in the 2013–2014 academic year. Data were collected with a Personal Identification Form and The Ethics Position Questionnaire. Obtained data were analyzed with Chi-square test, Confirmatory Factor Analysis, and Nested Analysis of Variance.Ethical considerations:Before conducting the research, approval was obtained from Ege University Clinical Research Ethics Committee in İzmir and written informed consent was taken from all the participants.Findings:There was no significant difference in the mean scores for the Ethics Position Questionnaire between the students in terms of years and fields of study. Although the mean scores for the subscale idealism did not differ between fields of study, the mean scores significantly differed between years of study. However, the mean scores for the subscale relativism did not differ in terms of years and fields of study.Discussion:Whether students are idealistic or relativistic in terms of ethical judgment will be effective in ethical decision-making skills during patient care. Therefore, we need to define the factors that influence students’ ethics position in the future.Conclusion:It is suggested that the courses and practices that teach students to be aware of their ethics position to create an ethical outlook can be placed in the curriculum in health schools.